2017
DOI: 10.1021/acsami.7b11530
|View full text |Cite
|
Sign up to set email alerts
|

The Detrimental Effects of Carbon Additives in Li10GeP2S12-Based Solid-State Batteries

Abstract: All-solid-state batteries (SSBs) have recently attracted much attention due to their potential application in electric vehicles. One key issue that is central to improve the function of SSBs is to gain a better understanding of the interfaces between the material components toward enhancing the electrochemical performance. In this work, the interfacial properties of a carbon-containing cathode composite, employing LiGePS as the solid electrolyte, are investigated. A large interfacial charge-transfer resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
288
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(300 citation statements)
references
References 57 publications
(123 reference statements)
10
288
2
Order By: Relevance
“…The sources of the data are listed in Table S2 (Supporting Information). It is apparent that the electrochemical performance of the dual shell structured LGPS@LNO@LCO overtakes previous results, especially the power density 6a,8a,21…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The sources of the data are listed in Table S2 (Supporting Information). It is apparent that the electrochemical performance of the dual shell structured LGPS@LNO@LCO overtakes previous results, especially the power density 6a,8a,21…”
Section: Resultssupporting
confidence: 66%
“…In S 2p spectra (Figure A), S of LGPS is highly oxidized to SS or CoS x in comparison with S spectra of pristine LGPS. In addition, sulfite and sulfate species were also detected, which is also caused by the oxidization of LGPS by LCO during the charge‐discharge process . Interestingly, the intensity of oxidization peaks is reduced with the inner LNO shell (Figure A, bottom), suggesting the inner shell LNO can alleviate the oxidization of LCO during the charge–discharge process.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Figure 6b,d, the changes in Coulombic efficiency for both all-solid-state batteries suggest that side reactions occur during the cycling of both cells, which may be associated with the decomposition of the solid electrolyte in both the cathode mixture and the solid electrolyte layer. 30 Previous research has reported that the decomposition of the solid electrolyte leads to the formation of products at the interface which can be expected to retard the Li + mobility and lead to a large interfacial charge transfer resistance during cycling. 3032 XPS data has shown that Li 6 PS 5 Cl has an electrochemical redox activity in the positive electrode, which can be partially oxidized into LiCl, P 2 S 5 , and polysulfides Li 2 S n upon charge.…”
Section: Resultsmentioning
confidence: 99%
“…30 Previous research has reported that the decomposition of the solid electrolyte leads to the formation of products at the interface which can be expected to retard the Li + mobility and lead to a large interfacial charge transfer resistance during cycling. 3032 XPS data has shown that Li 6 PS 5 Cl has an electrochemical redox activity in the positive electrode, which can be partially oxidized into LiCl, P 2 S 5 , and polysulfides Li 2 S n upon charge. 31 The introduction of LiI in the cathode mixture may work as a protective layer separating particles of the Li 2 S active material and the solid electrolyte, reducing the redox reaction, potentially explaining the better cycling performance of the 80Li 2 S–20LiI/Li 6 PS 5 Cl/In all-solid-state battery.…”
Section: Resultsmentioning
confidence: 99%